Employee’s Participation in Management of European, American and Japanese Companies - Joanna Radomska (Contemporary Economics)
The article describes the conditions of implementing the employee’s participation in management and analyzes the differences that are observed in European, Japanese and American companies. Moreover, Author shows different participation approaches, connected with culture, tradition and experiences of enterprises. That’s why there is no participation model, which could be recommended to be used in most global companies.